2008
DOI: 10.1021/ja7108486
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Spectroscopic, and Theoretical Elucidation of a Redox-Active Pincer-Type Ancillary Applied in Catalysis

Abstract: Pincer-type ligands are believed to be very robust scaffolds that can support multifarious functionalities as well as highly reactive metal motifs applied in organometallic chemistry, especially in the realm of catalysis. In this paper, we describe the redox and, therefore, noninnocent behavior of a PNP (PNP- = N[2-P(CHMe2)2-4-methylphenyl]2) pincer ancillary bound to nickel. A combination of structural, spectroscopic, and theoretical techniques suggests that this type of framework can house an electron hole w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 41 publications
13
110
1
6
Order By: Relevance
“…PBE0-dDsC computations used the TZ2P slater-type orbital basis set in ADF. 42,43 Solvation corrections, also computed at the PBE0-dDsC/TZ2P//M06/def2-SVP level, were determined in THF solvent using Klamt's Continuum Solvation The alternative escape-rebound pathway commences with structure E1, which, based analysis of the computed spin density is a doublet Ni(III) halide (Br) complex and not a Ni(II) ligand cation complex 45,46 owing to majority of the spin density being located on the nickel center (see SI Figure S10 Based on these findings, the bimetallic oxidative addition pathway is strongly preferred over the escape-rebound pathway based on its superior energetic profile (notably the barrierless association of the alkyl radical and small TS associated with reductive elimination of the alkyl-aryl product). In principle, these two pathways are interconnected by a reaction in which B1 abstracts a bromine atom from .…”
Section: Methodsmentioning
confidence: 99%
“…PBE0-dDsC computations used the TZ2P slater-type orbital basis set in ADF. 42,43 Solvation corrections, also computed at the PBE0-dDsC/TZ2P//M06/def2-SVP level, were determined in THF solvent using Klamt's Continuum Solvation The alternative escape-rebound pathway commences with structure E1, which, based analysis of the computed spin density is a doublet Ni(III) halide (Br) complex and not a Ni(II) ligand cation complex 45,46 owing to majority of the spin density being located on the nickel center (see SI Figure S10 Based on these findings, the bimetallic oxidative addition pathway is strongly preferred over the escape-rebound pathway based on its superior energetic profile (notably the barrierless association of the alkyl radical and small TS associated with reductive elimination of the alkyl-aryl product). In principle, these two pathways are interconnected by a reaction in which B1 abstracts a bromine atom from .…”
Section: Methodsmentioning
confidence: 99%
“…[81] It was demonstrated that ligand 4 can behave as a redox-based non-innocent ligand under certain reaction conditions.…”
Section: Nickelmentioning
confidence: 99%
“…30 . 42 This technique probes bound state transitions occur on low energy side the ligand K-edge, and involves excitation of ligand Is electrons into molecular orbitals of primarily metal charactt?r35 that also contain some ligand p character, due to covalent mixing. The intensity of the pre-edge transition is a direct measure of the ligand p orbital 3 Cpstr Full JACS_SAK Feb 152009 contribution to the primarily metal-based antibonding orbital.…”
Section: Introductionmentioning
confidence: 99%